A mutational analysis of the insulin gene transcription control region: expression in beta cells is dependent on two related sequences within the enhancer. - Karlsson, O (1987)
Cell-specific expression of the insulin gene is controlled by cis-acting DNA sequences located within approximately equal to 350 base pairs of the 5' flanking DNA immediately upstream from the transcription start site. Using synthetic oligonucleotides, we have constructed a systematic series of block replacement mutants spanning this region. No single sequence appears to be absolutely required for expression. However, three of the mutants exhibit 5-10 times less activity and several others show 2-3 times less. Simultaneous mutation of two of the most mutationally sensitive regions leads to virtual abolition of activity. These two elements are structurally related and presumably represent key components of the machinery determining the cell-specific expression of the insulin gene.